Design of single-symbol-decodable QOSTBC with full diversity based on pre-processing - CHENG Wen-jing; LIU Wei; DING Ding; WEI Ji-bo (Tongxin xuebao, 2010)
The method of pre-processing was applied to G-QOSTBC in order to reduce the complexity of decoding,which was single-symbol-decodable.Furthermore,an improved transmit strategy was proposed to achieve full diversity as well as maximum coding gain by constellation rotating and symbol interleaving.Simulation results show that the pro-posed code remarkably decreases the decoding complexity of G-QOSTBC while keeping the similar performance.In ad-dition,the proposed code has the same bit-error-rate（BER） performance as coordinate interleaved orthogonal design（CIOD）,but with a lower peak-to-average ratio（PAR）.